2022
DOI: 10.3390/nu14204342
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Patterns during Pregnancy with Gestational Hypertension: The “Born in Shenyang” Cohort Study

Abstract: The literature on maternal dietary patterns and gestational hypertension (GH) risk is largely ambiguous. We investigated the associations of maternal dietary patterns with GH risk among 1092 pregnant women in a Chinese pre-birth cohort. We used both three-day food diaries (TFD) and food frequency questionnaires (FFQ) to assess the diets of pregnant women. Principal components analysis with varimax rotation was used to identify dietary patterns from the TFD and FFQ, respectively. In total, 14.5% of the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Dietary patterns play an essential role in shaping overall health. Mateo-Orcajada and colleagues investigated levels of adherence to Mediterranean diet-one of the healthiest dietary patterns [1], while both Hu et al and Marinoni et al applied principal component analyses to identify specific dietary patterns among the participants [2,3]. Specifically, characteristics of physical activity and anthropometric measurements among 791 Spanish adolescents were described, categorized by levels of adherence to Mediterranean diet and body mass index (BMI) [1].…”
Section: Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary patterns play an essential role in shaping overall health. Mateo-Orcajada and colleagues investigated levels of adherence to Mediterranean diet-one of the healthiest dietary patterns [1], while both Hu et al and Marinoni et al applied principal component analyses to identify specific dietary patterns among the participants [2,3]. Specifically, characteristics of physical activity and anthropometric measurements among 791 Spanish adolescents were described, categorized by levels of adherence to Mediterranean diet and body mass index (BMI) [1].…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Specifically, characteristics of physical activity and anthropometric measurements among 791 Spanish adolescents were described, categorized by levels of adherence to Mediterranean diet and body mass index (BMI) [1]. Hu et al found that women's adherence to wheaten food-coarse cereals pattern in 21-24 gestational weeks was associated with a lower risk of gestational hypertension in one subgroup [2], although an association did not show a clear dose-response relationship among all 1082 participants, which requires further validations and subsequent investigations of potential mechanisms. Results from Marinoni's crosssectional study of dietary patterns on cognitive performance in 379 Italian children showed that a concurrent diet based on fish consumption may be associated with better verbal abilities and perceptual reasoning, diets based on meat and potatoes were associated with worse verbal abilities, and diets based on dairy products were associated with reduced processing speed [3].…”
Section: Dietary Patternsmentioning
confidence: 99%